Peer-Mediated Theatrical Engagement for Improving Reciprocal Social Interaction in Autism Spectrum Disorder - Corbett, Blythe A.; Qualls, Lydia R.; Valencia, Blythe; Fecteau, Stéphanie-M.; Swain, Deanna M. (Frontiers in Pediatrics, 2014)
The hallmark characteristic of autism spectrum disorder (ASD) is poor reciprocal social communication. Interventions designed to improve this core deficit are critically needed. Social skills interventions such as direct training, peer mediation, and video modeling have contributed to improvements in various social skills in children with ASD. This paper reviews existing social competence interventions available for children with ASD while highlighting hypothesized critical components for advancing, maintaining and generalizing skills, which include 1) peer mediation, 2) active learning, and 3) implementation in supportive, natural contexts. As a framework for these approaches, this conceptual paper describes SENSE Theatre, a novel intervention that combines trained peers that facilitate the performance-based theatrical treatment delivered in a supportive, community-based environment. A review of previous research shows early feasibility, setting the stage for more rigorous studies to aid in developing a standardized intervention package.